Current concepts in fracture reduction - Johnson, A. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Fracture management includes preoperative planning, implant selection, fracture reduction, implant application, and postoperative patient management. Fracture reduction can be one of the most challenging parts of the process. Time honoured principles, of gradual progressive traction and counter-traction, to anatomically restore the bone contour are still effective methods of fracture reduction (2). However, new concepts have emerged that incorporate: balanced anaesthesia techniques, image guided minimally invasive implant placement, bone alignment (rather than anatomical reconstruction) for comminuted fractures, and additional methods of achieving mechanical leverage (1, 3, 4, 16). The purpose of this paper is to discuss the decision making process for selecting fracture reduction techniques; and to describe those techniques for achieving and maintaining reduction for specific fractures.
Keywords: Fracture reduction